1997
DOI: 10.1542/peds.100.5.772
|View full text |Cite
|
Sign up to set email alerts
|

A Safety and Immunogenicity Comparison of 12 Acellular Pertussis Vaccines and One Whole-Cell Pertussis Vaccine Given as a Fourth Dose in 15- to 20-Month-Old Children

Abstract: Although differences were observed in reaction rates among the DTaP vaccines given as a fourth dose, the DTaP vaccines were, in general, associated with fewer adverse events than a US-licensed DTwP. For DTaP vaccines, fever; irritability; and injection site pain, redness, and swelling occurred more frequently after the fourth dose than after the third dose of the same vaccine in the primary series. No DTaP was consistently most or least reactogenic or immunogenic. Although serologic correlates of pertussis imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 14 publications
9
71
1
6
Order By: Relevance
“…It is reported that high levels of circulating antibodies against the B. pertussis virulence factors, such as PT, and PRN, may be important for protection. 4,27 Consistent with previous studies, 16,17 our results showed that mice immunized with WPVs had lower antibody production to PT, FHA and PRN compared with the purified APV group. Our results were also in agreement with the previous findings, 16,28 that high level secretion of IFN-g and no detectable of IL-4 by spleen cells from WPVs immunized mice observed indicated a typical Th1-type of response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is reported that high levels of circulating antibodies against the B. pertussis virulence factors, such as PT, and PRN, may be important for protection. 4,27 Consistent with previous studies, 16,17 our results showed that mice immunized with WPVs had lower antibody production to PT, FHA and PRN compared with the purified APV group. Our results were also in agreement with the previous findings, 16,28 that high level secretion of IFN-g and no detectable of IL-4 by spleen cells from WPVs immunized mice observed indicated a typical Th1-type of response.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3] Although the safe and effective, WPVs could be associated with some serious adverse events. 4 These reactions, although without permanent sequelae, may alarm parents and affect compliance with subsequent vaccinations. 5 In response to these concerns, acellular pertussis vaccines (APVs) were developed and first made available in Japan in 1980s for children at 2 y of age or older.…”
Section: Introductionmentioning
confidence: 99%
“…Acellular vaccines given as boosters to children aged 15-20 months 19 and 4-6 years 20 have also been reported to elicit more diverse immunologic responses than either whole-cell or acellular vaccines alone. 19,20 Our results help to support these findings, since children aged 1-4 years who received both vaccines experienced lower incidence rates than children of the same age who received either the wholecell or acellular vaccine alone.…”
Section: Discussionsupporting
confidence: 67%
“…Earlier studies [9][10][11][12][13][14][15][16] have demonstrated safety, and immunogenicity of DTPa vaccines as compared with DTPw vaccines when administered as booster doses in infants, preschool children and adults. Nevertheless, administration of the fifth dose of acellular vaccine in preschool children and adults has been associated with increased reactogenicity when compared to earlier doses of acellular vaccine.…”
Section: Discussionmentioning
confidence: 99%